Linear and jump frequency changes of a signal in a room - R. RUTKOWSKI; E. OZIMEK (Archives of Acoustics, 2014)
The paper discusses the deformation of the instantaneous frequency of signals with linear and jump frequency changes propagating in a room. The instantaneous frequency deformation in a room has been compared on the basis of theoretical and experimental data. It was found out that deformation of the instantaneous frequency for linear and jump frequency changes reached extreme value at the minima of the amplitude of the resultant signal. For linear frequency changes the deformation is proportional to the rate of frequency changes, and to the delay time of the reflected wave. In turn, for jump frequency changes, the deformation increase with an increase in the jump value. The instantaneous frequency reaches final value after a time equal to the reverbation time of a room.